Narrative Inquiry dari Pengalaman Siswa EFL dalam Pembelajaran Grammar dengan Menggunakan Quizizz sebagai Alat Penilaian Formatif - Binova, Lisye; Puspitaloka, Nina; Rahmawati, Maya (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aimed to investigate the experiences of EFL students in learning grammar through the use of Quizizz as a formative assessment tool. The study employed a narrative inquiry approach and gathering the data through reflective journals and interviews. The research site is SMA Negeri 17 Bekasi, with 6 participants consist of high, medium, and low achievements in English subject. The findings are thematically analyzed and categorized into strengths and weaknesses. In terms of strengths, this study highlighted Quizizz's practicality and ease of use, its engagement-enhancing features, and its motivational impact on students. However, in terms of weaknesses, this study discusses about its lack of impact on improving students' grammar skills, technical difficulties faced by students, and concerns related to rapid timing during assessments. The conclusion of this study is that by offering effective and interesting learning possibilities, Quizizz can be a useful tool for improving students' experiences with grammar.